COMPARATIVE ASSESSMENT OF GLYCEMIC, LIPID, AND INFLAMMATORY BLOOD PARAMETERS IN SYSTEMICALLY HEALTHY YOUNG AND OLDER ADULTS WITH PERIODONTITIS: A PRELIMINARY INVESTIGATION - Dr Shreya Shetty,; Dr Karunakar Shetty, (The Bioscan, 2025)
Background: Periodontitis has been established as the sixth complication of diabetes mellitus (DM). It shares a bidirectional relationship with Type 2 DM, both exacerbating systemic inflammation. Emerging research has also linked periodontitis with dyslipidemia and cardiovascular risks. This study aimed to compare glycemic, lipid, and inflammatory blood parameters between young and older systemically healthy adults with and without periodontitis. Methods: A total of 150 participants from ISNC Dental Clinics, Jeddah, KSA, were categorized into two age groups (23–35 years as young adults and 36–50 years as older adults). Participants were further divided into healthy and periodontitis subgroups. Clinical periodontal parameters and blood samples were obtained to assess glycemic levels (FBS, RBS, HbA1c), lipid profile (LDL, HDL, triglycerides, total cholesterol), and inflammatory markers (platelet and neutrophil counts). Data were analyzed using SPSS v21.0, employing t-tests and chi-square tests (p < 0.05). Results: Older periodontitis patients showed significantly higher plaque and bleeding scores compared to younger counterparts (p < 0.05). Inflammatory and glycemic parameters such as platelet counts, total cholesterol, triglycerides, and FBS were marginally higher in younger patients with periodontitis. Older patients with periodontitis exhibited significantly higher platelet counts and HDL levels, whereas bleeding scores were paradoxically lower. Younger periodontally healthy individuals showed elevated neutrophil counts and cholesterol levels versus older healthy individuals. No significant differences were observed in most glycemic and lipid values across age groups, though trends suggested systemic inflammatory differences. Conclusion: Age modifies the systemic inflammatory and metabolic response to periodontitis, with older adults demonstrating increased platelet and HDL responses and younger adults exhibiting higher lipid and glucose levels. These findings underscore the potential need for age-specific periodontal interventions to mitigate systemic risk.